Local income tax competition with progressive taxes and a fiscal equalization scheme - Florian Kuhlmey (University of Basel, Center of Business and Economics (WWZ), 2017)
This paper develops a model of local income tax competition with a progressive tax scheme and a built-in fiscal equalization scheme. Both aspects are central to policy makers: The progressivity for equity reasons, and the fiscal equalization to prevent a race to the bottom and to limit the degree of segregation of households according to income. The model is calibrated to the metropolitan area of Zurich (Switzerland), and policy evaluations reveal that a progressive tax scheme as the basis for local tax competition causes strong segregating forces that can only to some extent be compensated by the fiscal equalization scheme.
Keywords: H3; H7; R1; R2; 330; tax competition; income taxation; fiscal equalization; progressive taxation; segregation